2012
DOI: 10.25011/cim.v35i2.16288
|View full text |Cite
|
Sign up to set email alerts
|

The effects of selenium and vitamin E on lung tissue in rats with sepsis

Abstract: Purpose: In this study we examined the ability of selenium and vitamin E to prevent sepsis-induced changes in lung tissue. Methods: Fifty rats were divided into five groups: Group 1: Control group; Group 2: Sepsis group. In this group only cecal ligation and perforation (CLP) was performed. Group 3: Selenium group. An intraperitoneal dose of 100 µg selenium was given for the first two days followed by a daily dose of 40 µg for the next five days. CLP was performed the following day. Group 4: Selenium and vita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…Moreover, a more recent study suggested that the cytoprotective effects of silymarin can be attributed to normalization of lipid metabolism and preservation of mitochondrial energy production in high fat feeding-induced murine model of obesity [58]. Nevertheless, several studies illustrated the protective effects of other antioxidants such as N-acetylcysteine, resveratrol, vitamin E and curcumin on different organs following induction of sepsis [14,49,59,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a more recent study suggested that the cytoprotective effects of silymarin can be attributed to normalization of lipid metabolism and preservation of mitochondrial energy production in high fat feeding-induced murine model of obesity [58]. Nevertheless, several studies illustrated the protective effects of other antioxidants such as N-acetylcysteine, resveratrol, vitamin E and curcumin on different organs following induction of sepsis [14,49,59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these pathways are important targets to improve survival and prevent organ damage in septic patients. Indeed, several studies established the protective effect of antioxidants against sepsis-induced organ injury [7,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that coenzyme Q10 exerts a powerful antioxidant property by directly reacting with free radicals in the lysosome, the Golgi apparatus and the plasma membrane, in addition to the mitochondria (15). Although the effi cacy of antioxidant support treatment for sepsis has not been suffi ciently determined yet, there are many studies in which positive results have been obtained with antioxidant treatment (16,17,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies indicated that rat CRP is used for the marker of inflammation (2,12,18). In this study it was determined that CRP concentrations were raised after administrations in three group but this increase was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…CRP is a useful marker of inflammatory clinical situation (12). In the rat CRP has been studied as a marker of inflammation using experimental models (2,12,18). But some researchers investigated that CRP was less sensitive marker of inflammation in the rat than in the human (3,6).…”
Section: Introductionmentioning
confidence: 99%